2017
DOI: 10.1371/journal.pntd.0005667
|View full text |Cite
|
Sign up to set email alerts
|

Peridomestic Aedes malayensis and Aedes albopictus are capable vectors of arboviruses in cities

Abstract: BackgroundDengue and chikungunya are global re-emerging mosquito-borne diseases. In Singapore, sustained vector control coupled with household improvements reduced domestic mosquito populations for the past 45 years, particularly the primary vector Aedes aegypti. However, while disease incidence was low for the first 30 years following vector control implementation, outbreaks have re-emerged in the past 15 years. Epidemiological observations point to the importance of peridomestic infection in areas not target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 77 publications
(106 reference statements)
3
30
0
Order By: Relevance
“…The mosquito Ae. malayensis is widely distributed across South-East Asia with documented occurrence in Vietnam, Cambodia, Peninsular Malaysia and Singapore, Taiwan, the Andaman and Nicobar Islands, Laos, and Thailand [8][9][10][11]13 . Recently, a peridomestic population of Ae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mosquito Ae. malayensis is widely distributed across South-East Asia with documented occurrence in Vietnam, Cambodia, Peninsular Malaysia and Singapore, Taiwan, the Andaman and Nicobar Islands, Laos, and Thailand [8][9][10][11]13 . Recently, a peridomestic population of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a peridomestic population of Ae. malayensis in Singapore was shown to be competent for diverse arboviruses such as DENV, YFV and chikungunya virus 11,12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both species are also involved in the local transmission of chikungunya and Zika viruses (Ng et al 2009, Tan et al 2017, Ho et al 2017). Mendenhall et al (2017) reported that Ae. malayensis showed high susceptibility to dengue and chikungunya viruses and should be considered a potential vector.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus can be more competent at transmitting DENV and CHIKV than Ae. aegypti [2224]. Furthermore, Ae.…”
Section: Introductionmentioning
confidence: 99%